Performance-avoidance goal orientation and test anxiety: the mediating role of insecure striving, shame and self-compassion - Santos, Rita Ferreira (2020)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação